Jewish Identity and the Intercommunal Links between Diaspora Jewish Communities in the Second Temple Period - Trotter, Jonathan R. (Journal of ancient Judaism, 2021)
Abstract Many diaspora communities identify not only with a distant homeland but also with others distant from the homeland. How exactly do these intercommunal connections take place and contribute toward a shared identity? What specific aspects of diasporan identity are created or strengthened? What practices are involved? This study will begin to answer these questions through investigating two practices which were widespread among diaspora Jewish communities during the last two centuries of the Second Temple period (1st cent. B.C.E. –1st cent. C.E. ). First, we will show how sending offerings and making pilgrimages to the Jerusalem temple from these communities enabled regular intercommunal contact. Then, we will suggest some ways in which these voluntary practices reinforced a cohesive Jewish identity and the importance of the homeland, especially the city of Jerusalem and the temple, for many diaspora Jews, whether they lived in Alexandria, Rome, Asia Minor, or Babylonia.